Can Financial Soundness Indicators Help Predict Financial Sector Distress? - Pietrzak, Marcin (Washington, D.C. : International Monetary Fund, 2021)
This paper shows how the role of Financial Soundness Indicators (FSIs) in financial surveillance can be usefully enhanced. Drawing from different statistical techniques, the paper illustrates that FSIs generate signals that can accurately detect, with 4 to 12 quarters lead, emerging financial distress-as measured by tight financial conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Econometric and Statistical Methods; Financial Crises; Financial Markets and the Macroeconomy; General Financial Markets; Macroeconomic Policy, Macroeconomic Aspects of Public Finance, and General Outlook